Micromorphology of hesperidin crystals and ultrastructure of crystal-bearing cells in Metrodorea nigra, a neotropical Rutaceae species - Machado, Silvia Rodrigues [UNESP]; Bento, Karla Bianca de Deus [UNESP]; de Carvalho, Shelly Favorito [UNESP]; Canaveze, Yve; Rodrigues, Tatiane Maria [UNESP] (My University, 2023)
Researches on the developmental and morphological features of organic crystals in plants are relatively scarce. Hesperidin is a flavanone glycoside found abundantly in Rutaceae, mainly in Citrus fruits. Due to the variety of biological activities, hesperidin is one of the most promising bioflavonoids. We investigated the distribution, micromorphology and intracellular localization of hesperidin crystals in the vegetative organs of Metrodorea nigra, a neotropical Rutaceae tree. Additionally, we analyzed the ultrastructural organization of crystal-bearing cells. Bright field, epifluorescence and polarized-light microscopy, scanning (SEM) and transmission electron microscopy (TEM) analysis were performed. Hesperidin crystals appeared as needle-shaped crystals forming plumose clusters under SEM, and as acicular solitary crystal or aggregate yellow/brown twisted filaments inside cells under light microscope. Hesperidin and calcium oxalate crystals often occurred together in the epidermis and mesophyll tissues. Hesperidin crystals were abundant inside the phloem, while calcium oxalate crystals were absent in the vascular tissues. Phenolic substances occurred in all tissues, but they were abundant within vascular tissues. Flavonoid autofluorescence in blue color was associated with crystals in the cell walls and cytoplasm. The crystal-bearing cells exhibited extensive rough endoplasmic reticulum (RER) and associated vesicles filled with electron-dense materials, proliferation of the tonoplast and abundance of multilamellar bodies containing electron-dense or crystalline materials close to irregular plasmalemma. Our ultrastructural observations allow us to speculate that the RER and tonoplast membranes and associated vesicles appeared to be involved in the packaging and channeling of the materials toward the cell walls. Crystals of hesperidin and calcium oxalate occurred on the surface of common epidermal cells and glandular trichomes. The mechanisms of condensation, crystallization and extrusion of hesperidin crystal through the cell walls remain to be investigate, and could be an interesting subject for future studies.
Keywords: Flavonoids; Needle-shaped crystals; Organic crystals; Phenols; Scanning electron microscopy, Transmission electron microscopy